The influence of the natural environment and climate on life satisfaction in Australia - Ambrey, C; Fleming, C. M. (Griffith University, 2011)
The narrative of the twentieth century is dominated by three key trends: population growth, economic growth and urbanisation. Moreover, these trends are expected to continue well into the twenty-first century. Australia has not been immune to these trends. Australia’s population is projected to increase by 65% to over 35 million by 2049, and be accompanied by an average growth in per-capita Gross Domestic Product of 1.5% per annum. Much of this population and economic growth will be concentrated in an already highly urbanised environment. As a consequence, the natural environment in which the majority of Australians live is likely to undergo rapid change. It is useful, therefore, to better understand our relationship with this environment. Using data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, the Census of Population and Housing, and Geographic Information Systems (GIS), this paper examines the link between the natural environment and life satisfaction in Australia. The results indicate that certain natural environmental assets, such as national parks and the coastline are amenities, whereas creeks are disamenities. In regards to the influence of climate on life satisfaction, some unexpected results are found.
Discussion Paper Series in Economics and Business Statistics
Economics Discussion Papers
Keywords: Satisfaction; Social Capital -- Communities and Neighbourhoods; Lifestyle; Social engagement; Social Capital; Satisfaction; Communities and Neighbourhoods; Social engagement; Lifestyle